Construction of Participation in the Crime of Persecution in Indonesia - Idrus, Irwandhy; Sudiro, Ahmad (Law Development Journal, 2024)
In criminal law, the construction of participation refers to a situation where a person is involved in a criminal offense, not directly as the main perpetrator, but plays a role in the implementation of the criminal offense. This means that a person can be charged with a crime even though he/she did not physically commit the criminal act, as long as he/she fulfills the elements of participation. The problems faced in this study are how the predicate crime of the crime of persecution in the case of South Jakarta District Court Decision Number 4/Pid.Sus-Child/2023/PN.Jkt.Sel and how the participation in the South Jakarta District Court Decision Number 4/Pid.Sus-Child/2023/PN.Jkt.Sel. The research method used is normative juridical legal research. The research specification used in this research is descriptive analytical. This research uses primary, secondary and tertiary sources of legal material. The approaches used from several approaches above are the statute approach and the case approach and the analysis technique used is qualitative analysis. The results showed that predicate crime in a criminal offense, including persecution, are elements that must be proven legally to declare a person has committed the crime. This predicate serves as the basis for law enforcement to impose a sentence. It must be underlined that each case has different characteristics. Therefore, the application of the law in each persecution case will vary depending on the facts revealed in the trial. Victims of persecution are entitled to legal protection. Participation in the crime of maltreatment is a form of understanding a person's criminal responsibility in a criminal event and in this case, however, in this case, Child AG cannot be classified as “assisting in the commission” because he did not knowingly provide assistance to commit the crime of maltreatment, either before, during or after the maltreatment was committed. There was no conspiracy or providing facilities, information and other efforts in realizing the crime of maltreatment.